Gamma and beta bursts during working memory readout suggest roles in its volitional control - Mikael Lundqvist (Nature Portfolio, 2018)
Previously, the authors have shown that working memory can be maintained by brief gamma oscillation bursts. Here, the authors use a new task to further demonstrate the dynamics of gamma and beta oscillations in working memory readout, independent of behavioral response.